Factor structure of Islamic techniques for managing Occupational Stress Questionniare (ITMOQ) - Hashim, Che Noraini; Kayode, Bakare Kazeem (EuroJournals Publishing, Inc., 2010)
The school system is a green pasture for inexhaustible investigations for the purpose of enhancing academic achievement. This is particularly true, because factors and variables within the confines of educational activities appear also to be inexhaustible. One of such factor that attracted an investigation is 'occupational stress' as it affects school administrators and senior teachers. This study investigates the Islamic technique or methods use by administrators and senior teachers to manage stress at workplace. The aspects that were investigated include-- Solat, EEman, Remembrance, Imagination and meditation. Instrument used in this study consisted of (24 item) questionnaire developed by the researcher. A 5-point likert scale ranging from 1—'strongly disagree, 5—strongly agree' was used. Using a systematic sampling technique, a survey was conducted on 130 samples from the population of 200. The participants consisted of administrators and senior teachers from three International Islamic secondary schools in klang Valley area Malaysia. principal component analysis (PCA) with varimax rotation yielded a 5-factor solution with satisfactory psychometric properties. The result also revealed that ITMOQ is multidimensional measure of Islamic ways to manage stress. It is therefore concluded that even-though, ITMOQ has a wider applicability, the scale may serve has a special relevance to stress management techniques, and may be of use in research and in stress management programmes.